Fatigue life prediction of wire rope based on stress field intensity method. (November 2017) - Zhao, Dan; Liu, Shaogang; Xu, Qingtao; Shi, Feng; Sun, Wenyi; Chai, Liqin
Abstract: In the paper, on the basis of the stress field intensity method, the internal complex wingding structure of 6 × 31SW + FC type wire rope is analyzed and calculated. As a first step, considering the weakening speed of weight function in the stress field intensity method is too fast, a modification is presented to make it more suitable for the calculation of the fatigue life of wire rope. The load spectrum of the critical locations of wire rope is then established, based on the Costello mechanical model and the actual working conditions. Through the stress field intensity method, the time history curve of stress field is then obtained. Subsequently, the fatigue life of wire rope is calculated by using the linear cumulative damage theory of fatigue. The wire rope fatigue test rig is established, and the experimental value of the fatigue life of wire rope is compared with the theoretical calculation value. The results show that the experimental load of 90 t is the demarcation point of high and low cycle fatigue of wire rope, the theoretical values and the test results are close to each other in the fatigue cycle, which proves the effectiveness of the stress field intensity method in predicting the fatigue life of the wire rope. Highlights: The stress field intensity method is involved to predict fatigue life of wire rope. The definition of weight function in the stress field intensity method is modified. A fatigue test rig for wire rope under heavy load is designed.